Gut microbiota and urine metabolomics signature in autism spectrum disorder children from Southern China - Ziyu Huang; Ailing Wei; Hai Yuan; Shiqin Huang; Xiaolan Chen; Yunli Han; Xing Li (BMC Pediatrics)
Abstract Background and aim Autism spectrum disorder (ASD) is a neurodevelopmental disorder that may have long-term effects on individual development, family functioning, and social integration. This study aimed to determine the gut microbiota and urine metabolomics signature and identify the regional characteristics in ASD from Southern China. Methods We conducted a cohort study of 88 well-characterized participants from Guangxi Zhuang Autonomous Region in Southern China. Gut microbiota and urine metabolomics signature was explored by 16 S rRNA sequences and untargeted metabolomic profiles respectively. Results The gut microbial α-diversity of ASD were significantly lower than healthy controls. The β-diversity analysis indicated that the community structure in ASD group was obviously distinctive. Significant microbiota enriched in 5 sensitive species, Faecalibacterium prausnitzii, Bifidobacterium catenulatum, Blautia obeum, Lachnoclostridium sp., and Blautia sp. in ASD children. In addition, functional analysis of the gut microbiota revealed that the ATP-binding cassette and ABC-2 type transport system ATP-binding protein were closely associated with ASD. Notably, microbiota showing a positive correlation with Androstenedione, Stearamide, Oleamide, Cadaverine, Hexadecanamide, Orotic acid, Linoleic acid, Palmitoleic acid, Lauric acid, suggesting a potential association with the Arginine and proline metabolism pathway. Conclusion This study found lower α-diversity, unique β-diversity, enriched species, and positive correlations between microbiota and Arginine/Proline metabolis, which demonstrated typical signature of microbiota and metabolites discriminated Zhuang ethnic group ASD children of regional characteristics.